Effects of ginsenosides on sympathetic neurotransmitter release in pithed rats - Zhang Feng-Luan; Chen Xiu (Acta Pharmacologica Sinica; Vol 8, No 3 (May 1987): Acta Pharmacologica Sinica, 2016)
Dept Pharmacology, Hunan Medical College, Changsha 410008